Spy in the wild. [videorecording (DVD)] ([Publisher not identified], 2017)
How different are we to our animal cousins? In this highly entertaining series a new generation of spy cameras reveals just how similar we really are. Each episode is themed around a familiar aspect of our own live, love, intelligence, friendship and mischief. Meet the elephant aunts who act as midwives, the bowerbirds gathering trinkets to impress the ladies, the hippos having pedicures, the monkeys getting drunk and disorderly, and more.